Reduction of the potential for thermal damage during hip resurfacing. - Gill, H; Campbell, P; Murray, D; De Smet, K (2007)
Resurfacing arthroplasty of the hip is being used increasingly as an alternative to total hip replacement, especially for young active patients. There is concern about necrosis of the femoral head after resurfacing which can result in fracture and loosening. Most systems use a cemented femoral component, with the potential for thermal necrosis of the cancellous bone of the reamed femoral head. We used thermal probes to record temperatures close to the cement-bone interface during resurfacing arthroplasty. The maximum temperature recorded at the cement-bone interface in four cases was approximately 68 degrees C which was higher than that reported to kill osteocytes. A modified surgical technique using insertion of a suction cannula into the lesser trochanter, generous pulsed lavage and early reduction of the joint significantly reduced the maximum recorded cancellous bone temperature to approximately 36 degrees C in five cases (p = 0.014). We recommend the modified technique since it significantly reduces temperatures at the cement-bone interface.